Pengaruh Penggunaan Kapur Sirih Sebagai Perekat Terhadap Kekuatan Tekan Briket Batubara - Yuliyanto, Yuliyanto; Wahyudie, Illham Ary; Kon Phin, Lioe (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
The increasing dependence on fossil fuels drives the need for alternative energy solutions to reduce environmental impacts and reliance on petroleum. Coal, particularly anthracite, has emerged as one of the best options due to its abundant availability in Indonesia. However, coal combustion often results in the emission of harmful gases, requiring special handling. This study aims to develop coal briquettes using lime water as a binder. In addition to improving the mechanical characteristics of the briquettes, lime water is also intended to reduce sulfur gas emissions during the briquette combustion process. The briquettes were produced using a binder-to-water ratio (5:6, 5:7, 5:8, 5:9), pressing pressure (8, 9, 10 tons), and drying time (2, 4, 6 days). Compression testing was conducted following the ISO 844 standard using a Universal Testing Machine. The highest result in this study was 502 kPa (5.11 kg/cm²), achieved with a binder-to-water ratio of 5:9, a pressing pressure of 8 tons, and a drying time of 4 days. However, this result remains far below the SNI standard (50 kg/cm²).